USE OF MAGNESIUM IN OBSTETRICS: MYTHS AND FACTS - G. B. Dikke (Акушерство, гинекология и репродукция, 2017)
Aim: to elucidate the role of magnesium deficiency in obstetric complications and to characterize the ways to prevent them by using oral administration of organic magnesium salts.Materials and methods. We analyzed publications of the Cochrane society, recommendations of obstetrics communities, clinical studies published in official websites and other information available to the public.Results.According to two multicenter studies conducted in Russia in 2012 and 2013 (MAGIC and MAGIC 2), magnesium deficiency was diagnosed in 81.2% and 80.9% of pregnant women, respectively. Meta-analyzes of the data published by the Cochrane society showed that an oral administration of organic magnesium salts for 3 weeks caused a significant decrease or disappearance of leg cramps in 65.5% of pregnant women (vs 5.7% with placebo). Treatment with magnesium during the period before the 25th week of pregnancy reduced the risk of complications as follows: premature births – by 27%; births of low weight babies – by 33%; mother hospitalization – by 34%; risk of spontaneous abortion – by 62%. In all the studies where pregnant women took oral magnesium medications, there was a low incidence of side effects.Conclusion.Measures to prevent magnesium deficiency both at the stage of preparation for pregnancy and during gestation, starting from the first weeks, help avoid some complications and improves the outcomes for the fetus and the newborn.